The Ethics of Policing : New Perspectives on Law Enforcement - Mendieta, Eduardo; Jones, Ben, 1985- (Book collections on Project MUSE., 2021)
"This book offers a wide-ranging analysis of the current ethical challenges facing police and the institutions that oversee them, featuring contributions from leading experts in black studies, criminology, history, law, philosophy, political science, and sociology"--Provided by publisher.